2018
DOI: 10.1039/c8py00308d
|View full text |Cite
|
Sign up to set email alerts
|

An l-proline based thermoresponsive and pH-switchable nanogel as a drug delivery vehicle

Abstract: The synthesis and characterisation of a novel dual stimuli-responsive nanogel, based on thermoresponsive N-n-propylacrylamide and an L-proline based monomer acting as a pH-switcher, is reported here. The effect of the crosslinker/co-monomer ratios was studied to demonstrate the relationship between the chemical structure, degree of hydrophobicity and physico-chemical characteristics of the nanogels. Tailoring of the thermoresponsive properties was achieved by altering crosslinker N,N'-methylenebis (acrylamide)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 58 publications
5
32
0
Order By: Relevance
“…These materials combine the properties typical of polymeric nanoparticles, such as a small size and a high surface-to-volume ratio, with a soft character and the ability to form stable colloidal solutions. The choice of functional monomers and crosslinkers and their ratio enables a fine tuning of the physical and chemical properties of the gels [ 6 , 7 , 8 , 9 ] and the introduction of stimuli-responsive characteristics [ 10 , 11 , 12 , 13 , 14 ]. The most common approaches to prepare covalently crosslinked nanogels involve post-polymerization crosslinking, performed on reactive polymer side-chains, or crosslinking during polymerization using di- or multi- functional comonomers (crosslinker) [ 3 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These materials combine the properties typical of polymeric nanoparticles, such as a small size and a high surface-to-volume ratio, with a soft character and the ability to form stable colloidal solutions. The choice of functional monomers and crosslinkers and their ratio enables a fine tuning of the physical and chemical properties of the gels [ 6 , 7 , 8 , 9 ] and the introduction of stimuli-responsive characteristics [ 10 , 11 , 12 , 13 , 14 ]. The most common approaches to prepare covalently crosslinked nanogels involve post-polymerization crosslinking, performed on reactive polymer side-chains, or crosslinking during polymerization using di- or multi- functional comonomers (crosslinker) [ 3 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our group has been interested in NIPAM-based nanogels prepared by HDRP for a diverse range of applications, from drug delivery vehicles to sensors, due to their high solubility, colloidal stability, and biocompatibility [ 25 ], together with thermoresponsive properties [ 6 , 26 , 27 , 28 ]. Recently, we investigated the morphological changes resulting from variations in chemical structure of functional monomers and crosslinker content in a library of NIPAM and other acrylamide-based nanogels [ 6 ]. Interestingly, observations made during that research suggested an impact of monomer reactivity on the chemical composition of the polymeric matrices, and we decided to investigate this further.…”
Section: Introductionmentioning
confidence: 99%
“…The main characteristics of the poly( l -proline) (pPro) is that its tertiary amide group leads to significant lowering of the barrier for cis-trans amide isomerization [127]. Further, the l -proline-based nanogel reported as a successful pH-switcher [128]. The recent report based on pPro tri-helix macrocycles as nanosized scaffolds suggested that they were capable to probe the rearrangement of receptors on the cell surface and manipulated signalling or cell recognition as nanomedicine [129].…”
Section: Types Of Ph-responsive Polypeptidesmentioning
confidence: 99%
“…Hence, it is safe to state that the variation in VPTT values of these nanogels with different percentages of cross-linker is not a significant factor influencing the interactions. The increased structural rigidity due to higher crosslinker content, which results in nanogels with a higher degree of hydrophobicity [39], facilitates the interactions between the nanoparticles and the lipids, leading to increased depletion. This is consistent with the observation that lipid depletion is increased with temperature, as the nanogels become more hydrophobic.…”
Section: Interaction Of Nanogels With Pure Ceramide Lipid Multi-bilayersmentioning
confidence: 99%
“…Previous studies [39][40][41] suggested that water soluble benzyl alcohol can readily partition into lipid bilayers where it is known to orient itself with its hydroxyl group in the head group region (polar region) and its aromatic nucleus directed into the tail group region (apolar core) of the bilayer. When intercalated into a lipid bilayer, benzyl alcohol acts as a membrane fluidizer, increasing the fluidity and decreasing the lipid base transition temperature.…”
Section: The Effect Of Penetration Enhancer On the Interaction Of Nanmentioning
confidence: 99%